The how tough is WASH framework for assessing the climate resilience of water and sanitation - Guy Howard; Anisha Nijhawan; Adrian Flint; Manish Baidya; Maria Pregnolato; Anish Ghimire; Moti Poudel; Y. T. Eunice Lo; Subodh Sharma; Bizatu Mengustu; Dinku Mekbib Ayele; Abraham Geremew; et al. (2021)
Abstract Climate change presents a major threat to water and sanitation services. There is an urgent need to understand and improve resilience, particularly in rural communities and small towns in low- and middle-income countries that already struggle to provide universal access to services and face increasing threats from climate change. To date, there is a lack of a simple framework to assess the resilience of water and sanitation services which hinders the development of strategies to improve services. An interdisciplinary team of engineers and environmental and social scientists were brought together to investigate the development of a resilience measurement framework for use in low- and middle-income countries. Six domains of interest were identified based on a literature review, expert opinion, and limited field assessments in two countries. A scoring system using a Likert scale is proposed to assess the resilience of services and allow analysis at local and national levels to support improvements in individual supplies, identifying systematic faults, and support prioritisation for action. This is a simple, multi-dimensional framework for assessing the resilience of rural and small-town water and sanitation services in LMICs. The framework is being further tested in Nepal and Ethiopia and future results will be reported on its application.